In Vitro Validation of a Multiscale Patient-Specific Norwood Palliation Model. Issue 3 (May 2016) - Hang, Tianqi; Giardini, Alessandro; Biglino, Giovanni; Conover, Timothy; Figliola, Richard S.
Abstract : In Norwood physiology, shunt size and the occurrence of coarctation can affect hemodynamics significantly. The aim of the study was to validate an in vitro model of the Norwood circulation against clinical measurements for patients presenting differing aortic morphologies. The mock circulatory system used coupled a lumped parameter network of the neonatal Norwood circulation with modified Blalock–Taussig (mBT) shunt with a three-dimensional aorta model. Five postoperative aortic arch anatomies of differing morphologies were reconstructed from imaging data, and the system was tuned to patient-specific clinical values. Experimentally measured flow rates and pressures were compared with clinical measurements. Time-based experimental and clinical pressure and flow signals within the aorta and pulmonary circulation branches agreed closely (0.72 < R 2 < 0.95) for the five patients, whereas mean values within the systemic and pulmonary branches showed no significant differences (95% confidence interval). We validated an experimental multiscale model of the Norwood circulation with mBT shunt by showing it capable of reproducing clinical pressure and flow rates at various positions of the circulation with very good fidelity across a range of patient physiologies and morphologies. The multiscale aspect of the model provides a means to study variables in isolation with their effects both locally and at the system level. The model serves as a tool to further the understanding of the complex physiology of single-ventricle circulation.